Synthesis of a stable B2H5+ analogue by protonation of a double base-stabilized diborane(4) - Ciobanu, Oxana; Kaifer, Elisabeth; Enders, Markus; Himmel, Hans-Jörg (Angewandte Chemie. International edition, 2009)
Polarity of H+ reversed: The synthesis of [B2H3(hpp)2]+I−,a dinuclear borohydride with terminal and bridging H atoms (see picture; B yellow, N blue, C gray, H white, I purple), is made possible with the ligand hexahydropyrimidopyrimidate (hpp). In the course of the reaction the proton is converted into a hydride.